INDEPENDENCE LEARNING POLICY SURVEY: How is the Response of the Academic Community in Higher Education? - Wahyudi; Nur Anggraeni, Fitria (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The rapid progress in various aspects of life has changed the direction and trend of the world, so it needs a fast response and good adaptation, one of which is through improving the quality of education. The presence of the idea of ​​independent learning is an answer to the current changing times, in its curriculum it carries efforts to accelerate the adaptation of human resources to technological advances and changes in the global environment by becoming competent and competitive human resources. So this program encourages a practical learning process that hones applied skills and knowledge needed by the industrial world. On this basis, this research was conducted to see the readiness of the higher education academic community in responding to the independent learning policy. To be able to explain these objectives, then conducted research with a quantitative approach and descriptive analysis. The research sample was the academic community of Pamulang University, amounting to 1000 people using a simple random sampling technique. The results of the study explain that the concept of independent learning is considered good as a modern era learning model, which is oriented towards applicable scientific specifications. However, there are still many campus academics who are not aware of the implementation of this policy, so that the participation and involvement of the parties is not maximized.